The Effect of Technology-Based Management Learning on Children's Organizational Skills Development: A Meta-Analysis Approach - Luciana, Occe; Suharry, Suharry; Risnawati, Risnawati; Sjoraida, Diah Fatma; Hatidja, ST; Santosa, Tomi Apra; Nugraha, Aat Ruchiat; Sarnoto, Ahmad Zain; Panggabean, Tongam E; Kurniawan, Andri; Samuna, Samuna (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
For This study aims to determine the effect of technology-assisted management learning on children's organisational skills. This type of research is quantitative research with a meta-analysis approach. The inclusion criteria in this study are a) publications come from Google Scholar; ERIC, ScienceDirect, DOAJ, Wiley and Taylor of Francis, b) publications must be indexed by SINTA, Scopus and Web of Science, c) research topics must be relevant, d) research published in 2022-2024, e) publications must have complete data to calculate the effect size value. Data analysis with the help of the JASP application. The results of this study concluded that 1) 21 studies analysed were heterogeneously distributed; 2) there was a significant effect of technology-based management learning on children's organisational skills (p < 0.05; rRE = 1.25; 3) in this meta-analysis there was no publication bias. These findings indicate the effect of technology-based management learning on children's organisational skills with a very high effect size category.